Complementary Therapies to Improve the Quality of Sleep in the Elderly: A Systematic Review - M. Noor Ifansyah; Elok Faiqotul Himmah; Melinda Restu Pertiwi (Universitas Bondowoso, 2021)
Introduction: As humans get older, a degenerative aging process occurs which will have an impact on changes in humans. The changes that occur in the elderly can cause various kinds of disorders, one of which is sleep disturbance or insomnia. The aim of this systematic review is to gain a deeper understanding of complementary therapies to improve sleep quality in the elderly. Method: The design used by systematic review is that the reviewer looks for several articles through an electronic database, namely Scopus and ScienceDirect, the keywords used are